STUDI PERANCANGAN STRUKTUR BANGUNAN GEDUNG 4 LANTAI - ANDIKA, RIKO (KURVA S JURNAL MAHASISWA, 2017)
From structural engineering advances to the present, we have been able to design awide range of construction buildings both from the size of the difficulty in the construction. In theplanning of a building construction, it is important for the planner to know the function and the use ofthe building to the built, it is because by knowing the purpose and use of the building is expectedplanner can be more thorough in designing and planning both in terms of accuracy of the exactcalculation and quality as well cost efficient.The process of using SAP 2000 program, giving ease in designing ideal model structurebesides also advantage of usage of SAP 2000 can accelerate the process of calculation analysisaccurately.